Simplified Surface Treatments for Ceramic Cementation: Use of Universal Adhesive and Self-Etching Ceramic Primer - Guimarães, Heloísa A. B.; Cardoso, Paula C.; Decurcio, Rafael A.; Monteiro, Lúcio J. E.; de Almeida, Letícia N.; Martins, Wellington F.; Magalhães, Ana Paula R. (International Journal of Biomaterials, 2018)
The aim of this study was to evaluate the shear bond strength of resin cement and lithium disilicate ceramic after various surface treatments of the ceramic. Sixty blocks of ceramic (IPS e.max Press, Ivoclar Vivadent) were obtained. After cleaning, they were placed in polyvinyl chloride tubes with acrylic resin. The blocks were divided into six groups (n=10) depending on surface treatment: H/S/A - 10% Hydrofluoric Acid + Silane + Adhesive, H/S -10% Hydrofluoric Acid + Silane, H/S/UA - 10% Hydrofluoric Acid + Silane + Universal Adhesive, H/UA- 10% Hydrofluoric Acid + Universal Adhesive, MBEP/A - Monobond Etch & Prime + Adhesive, and MBEP - Monobond Etch & Prime. The light-cured resin cement (Variolink Esthetic LC, Ivoclar Vivadent) was inserted in a mold placed over the treated area of the ceramics and photocured with an LED for 20 s to produce cylinders (3 mm x 3 mm). The samples were subjected to a shear bond strength test in a universal test machine (Instron 5965) by 0.5 mm/min. ANOVA and Tukey tests showed a statistically significant difference between groups (p<0.05). The results of the shear strength test were H/S/A (9.61±2.50)A, H/S (10.22±3.28)A, H/S/UA (7.39±2.02)ABC, H/UA (4.28±1.32)C, MBEP/A (9.01±1.97)AB, and MBEP (6.18±2.75)BC. The H/S group showed cohesive failures, and the H/UA group was the only one that presented adhesive failures. The conventional treatment with hydrofluoric acid and silane showed the best bond strength. The use of a new ceramic primer associated with adhesive bonding obtained similar results to conventional surface treatment, being a satisfactory alternative to replace the use of hydrofluoric acid.